Influence of Plumbing Materials on Biofilm Formation and Growth of Legionella pneumophila in Potable Water Systems - Rogers, Julie (1994)
A two-stage chemostat model of a plumbing system was developed, with tap water as the sole nutrient source. The model system was populated with a naturally occurring inoculum derived from an outbreak of Legionnaires' disease and containing Legionella pneumophila along with associated bacteria and protozoa. The model system was used to develop biofilms on the surfaces of a range of eight plumbing materials under controlled, reproducible conditions. The materials varied in their abilities to support biofilm development and the growth of L. pneumophila. Elastomeric surfaces had the most abundant biofilms supporting the highest numbers of L. pneumophila CFU; this was attributed to the leaching of nutrients for bacterial growth from the materials. No direct relationship existed between total biofouling and the numbers of L. pneumophila CFU.